Real Time Zidane - Marchessault, Janine (Cinémas)

(untitled) (Cinémas, 2018)
While television editing was developed on the basis of switching between cameras, video editing was from the start difficult and cumbersome, and as such editing was often limited to linear blocky assemblage as opposed to cinematic montage and continuity editing. But what video did offer (contra film’s re-presentation) and what early video art deconstructed was the illusion of immediacy, durée, transmission and “real time.” This article will consider the construction of “real time” (an expression that comes from informatics, meaning time mediated through technology) in the single channel version of Zidane: A 21st Century Portrait by Douglas Gordon and Phillip Parreno. In many ways, this work can be seen as a manifestation or culmination of early video art’s critique of simultaneity, which Gordon and Parreno merge with television’s real time ideologies. Zidane was shot with seventeen different cameras fixed on one player. These real time views were mixed by the artists like a piece of music and a performance to create a twenty-first-century portrait of mediation.